Sœur Philomène, by the Goncourt brothers, from pages to stage (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
The aim of this article is to contribute to general knowledge about the premiere of the first two seasons of the Théâtre Antoine in 1887. More precisely, it aims to look at the adaptation for the theater of the novel Sœur Philomène (1861), written by the brothers Edmond and Jules de Goncourt, made by Jules Vidal and Arthur Byl, and mounted on the premiere of its second season. The conditions under which this adaptation was produced, its circulation in France and its reception by theatrical critics in the press are thus questioned. This makes it possible to reconstruct, present and analyze the dynamics of tensions between different generations of agents active in the literary field and the performing arts field, who were engaged in the conception and establishment of the Théâtre Antoine.
Keywords: theatrical adaptation; Sœur Philomène; Goncourt Brothers; André Antoine; Théâtre Libre